Practical tools to identify short children born small-for-gestational-age eligible for rhGH treatment according to Italian regulation - Gianluca Tornese; Flavia Pricci; Maria Chiara Pellegrin; Marika Villa; Daniela Rotondi; Elvira Agazio; Egidio Barbi (BMC, 2019)
Abstract Recombinant human growth hormone (rhGH) is an approved and effective treatment for short children born small for gestational age (SGA). Prevalence of children eligible for treatment as SGA is reported to be 1:1800. The latest data from the National Registry of Growth Hormone therapy (RNAOC) showed that the number of children treated with SGA indication is still small (prevalence 0.37/100,000) and these children are significantly less reported than those treated for growth hormone deficiency (GHD), although GHD prevalence is 1:4000-1:10,000. This means that many short children born SGA are still not properly identified, and therefore not treated with rhGH, or misdiagnosed as GHD. This article provides some practical tools for the identification of children eligible for rhGH treatment.